Analysis of Potential Fire Due to Short Current in Semi-permanent Buildings at Tinumbu Street in Aisle 148-149 Makassar City - Rahmania Rahmania; Adriani Adriani; Rohana Rohana (Elkha: Jurnal Teknik Elektro)
Fires can occur if several other factors are met  heat sources, flammable materials and oxygen. The biggest potential cause of fires in buildings is electricity. This research aims to prove whether electrical short circuits trigger fires in residential homes or semi-permanent buildings, especially in electrical installation equipment. This type of research is quantitative using experimental methods, which are descriptive analysis to determine the effect of a particular treatment on other treatments under controlled conditions, to find out for sure the main cause of the fire. This research show that the mothers' knowledge is quite limited regarding the use of household electricity and the tools used are old enough to cause short circuits. This is also triggered by the use of electrical installations that do not meet PUIL 2000 and SNI standards. Researchers need to provide education to residents, especially housewives, about the effectiveness of using electricity at different times of the day. An explanation of the load distribution system for electrical devices is a top priority in this education. In this education, various forms of explanation and direction are provided regarding the importance of saving energy during peak hours and the importance of knowing the use of energy-saving products (LED lights). With the program to use environmentally friendly and energy efficient household electricity, mothers' understanding of the concept of environmentally friendly PLN will be more developed and more efficient in terms of welfare and family comfort from various environmental threats due to electricity disturbances.